Natural Alkaloids (Caffeine, Theobromine, and Theophylline) as Dielectric Capping Layers for Gold and Aluminum Gate Electrodes in Low Operating Voltage Organic Field-Effect Transistors - Irimia, Cristian Vlad; Yumusak, Cigdem; Ban, Boyuan; Leeb, Elisabeth; Mayr, Felix; Schimanofsky, Corina; Mardare, Andrei Ionut; Molnar, Maximilian Alexander; Teichert, Christian; Sariciftci, Niyazi Serdar; Irimia-Vladu, Mihai (IEEE journal on flexible electronics, 2025)
Three natural alkaloids, caffeine, theobromine, and theophylline, are reported for their application as dielectric layers in organic field-effect transistors (OFETs) utilizing both gold and aluminum gate electrodes. After careful purification of the materials, a detailed analysis using X-ray diffraction spectroscopy (XRD), Fourier transform infrared (FTIR) spectroscopy, contact angle (CA), impedance spectroscopy, amplitude-modulated kelvin probe force microscope (AM-KPFM), and cyclic voltammetry (CV) is performed. OFET devices operating at typical voltages between 2 and 4 V have been fabricated with the investigated alkaloid films processed via blade coating (caffeine) or vacuum processing (theobromine and theophylline). The dielectric properties of these three alkaloids are measured in impedance spectroscopy and negligible leakage currents are observed when deposited in thin films as dielectric layers in OFETs on aluminum electrodes. There is a high tendency for these molecules to crystallize and form uneven surfaces. When the thin-film forming properties are carefully controlled, organic alkaloids can be employed in applications involving implantable, transient, or even edible electronics.